Bibliometric Study on Digital Education of Knowledge and Skill using VOS Viewer - Istichomah, Istichomah; Sansuwito, Tukimin Bin; Situmorang, Benri (International Journal of Educational Qualitative Quantitative Research, 2024)
The bibliometric analysis of publications connected to nursing education methods and digital media is still restricted. Thus, there needs to be more understanding of practices and concepts. This study aims to determine the trend in publications and visualization of nursing learning techniques and digital media. The bibliometric method with policy-related scientific publication data from 2017 to 2024 uses a VOS viewer. The publications evaluated came from the Google Scholar database: 200 articles, 13 from Scopus, and 14 from PubMed. The literature search was conducted online in March 2024 using keywords: knowledge, skill, and digital education. The articles were downloaded in RIS format and processed with a VOS viewer to visualize and analyze patterns in bibliometrics. VOS viewer can generate network, overlay, and density visualization maps. Following analysis by the VOS viewer software, 8 clusters were identified in mapping all themes (light purple, brown, orange, Tosca, purple, yellow, blue, green, and red). The clusters demonstrated a link between one issue and another. The thickness of the connecting line indicated the strength of pairs of topic areas or keywords. The mapping results presented above reveal the number of terms and other term associations associated with digital education. Future academics can develop themes that have yet to be explored by considering the density of topics offered and paying regard to duty and ethics in education. This research contributes to providing information on the use and implementation of technology in nursing education in the digital era.